Operationalizing heterogeneity in poststructuralist discourse theory: the heterogeneous logics of international trade politics. Issue 6 (2nd November 2021) - Jacobs, Thomas
ABSTRACT: Ever since an intense theoretical debate over a decade ago, the concept of heterogeneity has had a well-established place within poststructuralist Discourse Theory. It captures the interactions between the heart of the space of representation and its margins, between excluded excess and manifest presence; and conceptualizes particularities, differential remainders, and discursive exteriority. The analytical implications of heterogeneity remain underexploited, however. This contribution makes the case that one way to operationalize the notion of heterogeneity in empirical research is by tracing its strategic effects. Since heterogeneity constitutes 'the primary terrain within which homogeneizing logics operate', heterogeneous dynamics like the 'incorporation of new demands' and 'the exclusion of others who were previously present' affect and shape the availability and feasibility of political strategies. This contribution first provides an extensive definition of heterogeneity drawing on the original debate that gave the concept prominence. An approach that captures and explains the strategic effects of heterogeneity is then developed through the integration of heterogeneity into the logics framework. Finally, this approach is illustrated through an exploration of the politics of international trade.